Phytochemical profile and GC-MS analysis of Flacourtia jangomas fruit for therapeutic applications - PRADIP DEBNATH; BITHY RANI SHILL; KISHORE KUMAR SARKAR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Debnath P, Shill BR, Sarkar KK. 2025. Phytochemical profile and GC-MS analysis of Flacourtia jangomas fruit for therapeutic applications. Biodiversitas 26: 6140-6150. The application of natural compounds and their structural analogs plays a pivotal role in modern pharmacotherapy. Flacourtia jangomas, a member of the Salicaceae family, is known for its traditional medicinal uses and pharmacological potential. The present study aimed to characterize the phytochemical constituents of hydroalcoholic whole-fruit extracts of F. jangomas through preliminary phytochemical screening and Gas Chromatography-Tandem Mass Spectrometry (GC-MS/MS). Qualitative analysis revealed the presence of alkaloids, carbohydrates, flavonoids, glycosides, saponins, and terpenoids. GC-MS/MS analysis identified 23 bioactive compounds, with Glycidyl Palmitate (30.92%) and 5-Hydroxymethylfurfural (13.92%) being the most abundant. Other compounds included 3-Methylthiophene-2-carboxamide (5.46%), (2R,6R)-2-Heptyl-6-Methylpiperidine (2.77%), Sebacic acid, isohexyl 2-naphthyl ester (1.72%), Sedoheptulosan (1.69%), 2(5H)-Furanon (1.53%), 1,2-Ethanediol, Dipropionate (1.27%), 2-Furancarboxylic Acid, Hydrazide (1.15%), and Trans-2-Methyl-4-N-Butylthiane, S,S-Dioxide (1.09%), and others in lower concentrations. A number of compounds identified in the sample through GC-MS/MS analysis have been previously reported to exhibit antioxidant properties. The presence of antioxidant, anti-inflammatory, and antidiabetic metabolites such as glycidyl palmitate, 5-hydroxymethylfurfural, eugenol, and coumarin supports its traditional medicinal uses. These results highlight the potential application of F. jangomas fruit extracts in the development of functional foods, nutraceuticals, and plant-based pharmaceuticals aimed at managing oxidative stress-related disorders, metabolic diseases, and chronic inflammatory conditions.